2022
DOI: 10.1111/jdi.13783
|View full text |Cite
|
Sign up to set email alerts
|

Association of body mass index with risk of prediabetes in Chinese adults: A population‐based cohort study

Abstract: Aims/Introduction Overweight and obesity in adults are strongly associated with an increased risk of prediabetes, and this study set out to gain a better understanding of the optimal body mass index (BMI) range for assessing the risk of prediabetes in the Chinese population. Materials and Methods The cohort study included 100,309 Chinese adults who underwent health screening. Participants were divided into six groups based on the cut‐off point for BMI recommended by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…The probability of prediabetes-free survival gradually increased with increasing eGFR, suggesting that the group with the highest eGFR had the lowest risk of pre-diabetes. A recent study by Zou et al identified 12.31% of participants with new-onset pre-diabetes over a median observation period of 3.1 years (37). Our study found that pre-diabetes incidence was 10.58% after a median follow-up of 3.0 years in the population with physical examination in the Chinese community.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…The probability of prediabetes-free survival gradually increased with increasing eGFR, suggesting that the group with the highest eGFR had the lowest risk of pre-diabetes. A recent study by Zou et al identified 12.31% of participants with new-onset pre-diabetes over a median observation period of 3.1 years (37). Our study found that pre-diabetes incidence was 10.58% after a median follow-up of 3.0 years in the population with physical examination in the Chinese community.…”
Section: Discussionsupporting
confidence: 55%
“…The incidence of pre-diabetes was slightly lower in our study population. By comparing people in both cohorts, those without lipid parameters were excluded from the study by Zou et al (37). The final sample size was 100309, and their study had a maximum follow-up time of about 6 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All 8 (100%) patients with mild NPDR retinopathy were obese. With similar BMI categorization, it has been reported that the increase in BMI was associated with an increased risk of prediabetes 19 and positively associated with DR. 20 Our study also showed that 37.5% of mild NPDR retinopathy patients were hypertensive.…”
Section: Discussionmentioning
confidence: 79%
“…In addition, weight gain is also a high-risk risk factor for prediabetes ( 21 ). Several studies have demonstrated that BMI follows a positive dose-response relationship with the risk of prediabetes ( 47 49 ). Therefore, we hypothesized that a reduction in BMI may be associated with an increased probability of regression to normoglycemia from prediabetes.…”
Section: Discussionmentioning
confidence: 99%